ANALISIS IMPLEMENTASI PRAKTIK AKUNTANSI YANG BERKELANJUTAN PADA LAPORAN KEUANGAN UMKM SOE77 KITCHEN BESUKI – SITUBONDO - Siti Alfiyah (CV. ADIBA AISHA AMIRA, 2023)
Accounting is a means of infrastructure that can produce financial reports for parties in need within the company. This accounting is needed to determine the financial condition of the company. However, not many companies have not implemented accounting in their financial reporting. Especially at umkm. Supposedly, as SMEs that have developed, such as UMKM Soe77 Kitchen, they need to have accurate and transparent financial reports so that they can find out about the financial development of their business. Therefore, the application of proper accounting is very important in preparing their financial reports. Because MSMEs have been launched as a support for the nation's economy, so financial accuracy and business development conditions are very much needed. The purpose of this journal is to identify and analyze the application of accounting in the financial statements of UMKM Soe77 Kitchen Besuki-Situbondo